Remuneração variável no serviço público - Marin, Lauro Kuester (2018)
With the economic and financial crisis that has hit the world since 2008 and in Brazil with more intensity starting in 2014, reducing the resources for the provision of public services and for financing the functioning of the State and even before, from the economic crises that began in the twentieth century, the public service has sought private management models that reduce the costs of maintaining the public machine, improve service delivery, and create incentives for satisfaction in the work environment and commitment to the results of delivered services. The variable remuneration is one of these models brought from the private initiative to the public service, which has had a lot of contestation in the last decades (OECD, 2005, PERRY, ENGBERS, JUN, 2009; BOWMAN, 2010; WEIBEL, ROSK, OSTERLOH, 2010) but still holds in the governments of underdeveloped countries such as Brazil, an attraction as a model of compensation for people that would bring good results. The State of São Paulo has adopted in large part the careers of its staff members the variable compensation linked to collective goals of productivity starting in 2008, and in the present year - 2018 - ten years of its implementation are completed, which is why This research investigated its impacts according to the opinion of the managers of the affected servers and their class representatives, to verify if it is an alternative to improve the provision of public services and if it is also a form of remuneration that brings to the servers greater personal satisfaction and commitment in the job. The results of the research, with interviews in thirty-six servers, showed that it did not promote greater productivity in the last ten years in the five careers surveyed (Three from the Education Department, one from the Public Security Secretariat and one from the Treasury Department) and which also did not promote improvement in the personal satisfaction of the servers in the work environment and commitment to the results. However, it was verified that it managed to change the focus of the bureaucratic process servers, which constitutes a great problem in public administration, for results, which really matters to society